Investigating the Connection Between Endogenous Heme Accumulation and COX2 Activity in Cancer Cells - Destefanis, Francesca; Fiorito, Veronica; Altruda, Fiorella; Tolosano, Emanuela (Frontiers in Oncology, 2019)
Heme, an iron-containing porphyrin, is fundamental for a variety of functions in cell homeostasis. Nevertheless, recent data indicate that dysregulation of heme metabolism might promote tumorigenesis. The intracellular heme pool is finely regulated through the control of heme synthesis, degradation, incorporation into hemoproteins and trafficking across membranes. All these processes might be potentially targeted to alter endogenous heme content in order to counteract cancer growth. Nevertheless, these putative therapeutic interventions have to take into account the possibility of undesired side effects, such as the over-activation of heme-dependent enzymes involved in cancer. Among them, cyclooxygenase-2 is a prostaglandin-producing hemoprotein, induced during inflammation and in different types of tumor, particularly in colorectal cancer. The aim of this study was to evaluate whether modulation of endogenous heme may affect cyclooxygenase-2 expression and activity, taking advantage of two different approaches able to alter heme levels: the silencing of the heme exporter Feline Leukemia Virus subgroup C receptor 1 and the induction of heme synthesis by 5-aminolevulinic acid administration. Our data demonstrate that the down-regulation of the heme exporter in colorectal cancer cells does not affect cyclooxygenase-2 expression and activity. Conversely, 5-aminolevulinic acid administration results in decreased cyclooxygenase-2 expression. However, the overall cyclooxygenase-2 enzymatic activity is maintained. The present work sheds light on the complex modulation of cyclooxygenase-2 by endogenous heme and support the idea that targeting heme metabolism could be a valuable therapeutic option against cancer.